Elective discontinuation of Larotrectinib in pediatric patients with TRK fusion sarcomas and related mesenchymal tumors - Mascarenhas, Leo; DuBois, Steven G.; Albert, Catherine M.; Bielack, Stefan; Orbach, Daniel; Federman, Noah; Geoerger, Birgit; Nagasubramanian, Ramamoorthy; Zhang, Yizhou; Chisholm, Julia; Gallego Melcon, Soledad; Goto, Hiroaki; et al. (Journal of clinical oncology, 2025)
Larotrectinib is a highly selective tropomyosin receptor kinase (TRK) inhibitor with efficacy in children with TRK fusion tumors. We evaluated patient outcomes after elective discontinuation of larotrectinib in the absence of disease progression in a protocol-defined wait-and-see subset analysis of eligible patients where treatment resumption with larotrectinib was allowed if disease progressed. We also assessed the safety and efficacy of larotrectinib in all pediatric patients with sarcoma. This cohort included 91 patients (younger than 18 years) from two clinical trials: infantile fibrosarcoma (49), other soft tissue sarcomas or related mesenchymal tumors (41), and bone sarcoma (1). Treatment-related adverse events were of maximum grade 1 or 2 in 25% and 25% of patients, respectively. The overall response rate was 87% (95% CI, 78 to 93). In the wait-and-see analysis, 47 patients discontinued larotrectinib. Median time from discontinuation to disease progression was not reached. Sixteen patients had tumor progression during the wait-and-see period. All 16 patients resumed larotrectinib, and 15 (94%) achieved disease control, with 11 objective responses. Larotrectinib continues to demonstrate durable responses with favorable safety in children with TRK fusion sarcomas. Treatment discontinuation is feasible in select patients with objective response and clinical benefit noted in those who have disease progression after elective treatment discontinuation.